High Antioxidant Capacity of Lacticaseibacillus paracasei TDM-2 and Pediococcus pentosaceus TCM-3 from Qinghai Tibetan Plateau and Their Function towards Gut Modulation - Tingyu Yang; Xueni Fan; Diantong Li; Tingting Zhao; Dan Wu; Zhenjiang Liu; Danfeng Long; Bin Li; Xiaodan Huang (Foods, 2023)
Probiotic supplementation is a key therapeutic strategy for promoting gut health and maintaining gut homeostasis by modulating functional microbiota. In this study, we isolated two lactic acid bacteria (LAB) strains, Pediococcus pentosaceus TCM-3 and Lacticaseibacillus paracasei TDM-2, from Qinghai-Tibetan plateau, and evaluated their probiotic properties and antioxidant bioactivity. In which, TDM-2 had higher T-AOC activity than either TCM-3 or LGG (4.10 μmol/mL vs. 3.68 and 3.53 μmol/mL, respectively, p < 0.05). These strains have shown high antioxidant activity compared to the LAB strains and were found to be acid and bile salt tolerant, confronting the safety issues of antibiotic resistance and the capability of surviving in simulated gastric and intestinal juices. In vitro fermentation experiments with human gut microbiota revealed significant differences in microbial community composition between samples supplemented with TCM-3 and TDM-2 and those without. The addition of these two strains resulted in an enrichment of beneficial taxa, such as the Pediococcus, Lactobacillus, and Clostridium_sensu_strictos at the genus level, and Firmicutes and Proteobacteria at the phylum level. Notably, the TCM-3 group exhibited higher short-chain fatty acid production than the TDM-2 group and untreated controls (acetic acid at 12 h: 4.54 mmol L−1 vs. 4.06 mmol L−1 and 4.00 mmol L−1; acetic acid at 24 h: 4.99 mmol L−1 vs. 4.90 mmol L−1 and 4.82 mmol L−1, p < 0.05). These findings demonstrate that LAB supplementation with high antioxidant capacity and probiotic properties can promote gut health by modulating functional microbiota and is enriching for beneficial taxa. Our study provides guidance for therapeutic strategies that use novel LAB strains to maintain gut homeostasis and functional microbiota modulation.